2012
DOI: 10.1371/journal.pone.0046993
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of Abandoned Land by Juniperus thurifera Is Mediated by the Interaction of a Diverse Dispersal Assemblage and Environmental Heterogeneity

Abstract: Land abandonment is one of the most powerful global change drivers in developed countries where recent rural exodus has been the norm. Abandonment of traditional land use practices has permitted the colonization of these areas by shrub and tree species. For fleshy fruited species the colonization of new areas is determined by the dispersal assemblage composition and abundance. In this study we showed how the relative contribution to the dispersal process by each animal species is modulated by the environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 55 publications
1
41
0
6
Order By: Relevance
“…Although a large proportion of the seeds lands underneath conspecifics, the fraction that escapes from the neighborhood of T. baccata trees is crucial for subsequent stages of the species' population dynamics (González- Schupp & Jordano, 2011). As the main driver of seed flow, frugivorous birds play a pivotal role for yew populations, however carnivorous mammals should not be neglected since they contribute to the recolonization process through long distance dispersal (Escribano-Avila et al, 2012). Conservation and management practices should focus on maintaining a frugivore assemblage as diverse as possible to allow for complementary seed dispersal (García & Martínez, 2012;Escribano-Avila et al, 2014), thus increasing the chance for a seed to reach favourable conditions and acus preferentially forage around the focal trees, sometimes in big flocks (T. iliacus), and fly short distances towards the neighbouring microhabitats (Martínez et al, 2008), thus most likely dispersing the seeds within forest patches.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a large proportion of the seeds lands underneath conspecifics, the fraction that escapes from the neighborhood of T. baccata trees is crucial for subsequent stages of the species' population dynamics (González- Schupp & Jordano, 2011). As the main driver of seed flow, frugivorous birds play a pivotal role for yew populations, however carnivorous mammals should not be neglected since they contribute to the recolonization process through long distance dispersal (Escribano-Avila et al, 2012). Conservation and management practices should focus on maintaining a frugivore assemblage as diverse as possible to allow for complementary seed dispersal (García & Martínez, 2012;Escribano-Avila et al, 2014), thus increasing the chance for a seed to reach favourable conditions and acus preferentially forage around the focal trees, sometimes in big flocks (T. iliacus), and fly short distances towards the neighbouring microhabitats (Martínez et al, 2008), thus most likely dispersing the seeds within forest patches.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their potential to disperse the seeds over long distances (Jordano et al, 2007;Matías et al, 2009), their role as efficient seed dispersers remain unclear. Indeed, Peredo et al (2013) found that they deposited a large fraction of the seeds into unsuitable microhabitats for germination and seedling establisment, such as latrines in the case of badgers, a microsite where seeds are probably faced to overcrowding and recurrent disturbance (but see Escribano-Avila et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endozoochorous dispersal in junipers is carried out by different groups of birds and carnivore mammals that play complementary roles and make dispersal highly effective (Escribano‐Ávila et al. , ), thereby promoting the early colonization of abandoned fields. In our study system, birds are responsible for dispersal services at the local scale (tens to a few hundred meters; Breitbach et al.…”
Section: Discussionmentioning
confidence: 99%
“…), whereas carnivores such as red fox ( Vulpes vulpes ) or stone marten ( Martes foina ) favour long‐distance seed dispersal, which can frequently exceed 1–2 km (Escribano‐Ávila et al. ). In contrast, wind‐dispersed pine seeds reach shorter distances from the mother plant (around 30 m on average; Ribbens et al.…”
Section: Discussionmentioning
confidence: 99%